2019
DOI: 10.1021/acsnano.8b07625
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Detection of Singlet Fission in Single Crystal Tetracene Transistors

Abstract: We present the electrical detection of singlet fission in tetracene by using a field-effect transistor (FET). Singlet fission is a photo-induced spin-dependent process, yielding two triplet excitons from the absorption of a single photon. In this study, we engineered a more deterministic platform composed of an organic single crystal FET rather than amorphous or polycrystalline FETs to elucidate spin-dependent processes under magnetic fields. Despite the unipolar operation and relatively high mobility of singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 43 publications
1
22
0
Order By: Relevance
“…[43] The MFEs was also used to confirm the electrical detection of singlet fission which generated photocurrent in an OFET. [23,24] Figure 10 illustrates the photo-induced current as well as magnetoconductance (MC) measurements in a single crystal tetracene FET. As displayed in Figure 10B, the photo-enhanced current was observed in the transistor and the MFEs was investigated to understand the origin of the photo-induced current; As shown in Figure 10C, a large photo-induced MC was detected in the transistor and in the study, the features of singlet fission in MC data was qualitatively explained by a numerical simulation adopting the singlet fission model based on Equation (2).…”
Section: Applications and Utilizations Of Magnetic Field Effects (Mfementioning
confidence: 99%
See 4 more Smart Citations
“…[43] The MFEs was also used to confirm the electrical detection of singlet fission which generated photocurrent in an OFET. [23,24] Figure 10 illustrates the photo-induced current as well as magnetoconductance (MC) measurements in a single crystal tetracene FET. As displayed in Figure 10B, the photo-enhanced current was observed in the transistor and the MFEs was investigated to understand the origin of the photo-induced current; As shown in Figure 10C, a large photo-induced MC was detected in the transistor and in the study, the features of singlet fission in MC data was qualitatively explained by a numerical simulation adopting the singlet fission model based on Equation (2).…”
Section: Applications and Utilizations Of Magnetic Field Effects (Mfementioning
confidence: 99%
“…As displayed in Figure 10B, the photo-enhanced current was observed in the transistor and the MFEs was investigated to understand the origin of the photo-induced current; As shown in Figure 10C, a large photo-induced MC was detected in the transistor and in the study, the features of singlet fission in MC data was qualitatively explained by a numerical simulation adopting the singlet fission model based on Equation (2). [24] Since it has been shown that an external magnetic field can alter the singlet fission process by its MFEs, it is natural to explore the addition of a permanently existing magnetic field source, such as a ferromagnetic material to the molecular system to find out how it influences the singlet fission process. Figure describes the work on the thin film structure made of two layers, (ferromagnetic) cobalt and tetracene on a glass substrate.…”
Section: Applications and Utilizations Of Magnetic Field Effects (Mfementioning
confidence: 99%
See 3 more Smart Citations